Georgian Verse: Path of Development, Nature, Researchers : A Brief Survey - Tamar Barbakadze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Genesis of Georgian verse goes back to pre-Christian times. In Old Georgian written monuments fixed rhyme and metre have been revealed much earlier than in Indo-European verse. The history of Georgian verse knows four reformers: Shota Rustaveli, David Guramishvili, Nikoloz Baratashvili and Galaktion Tabidze. Georgian verse adopted Oriental and European stable verse forms (iambus, mukhambazi, sonnet, etc.), though its main metre is still established: shairi (4444, 5353//3535), shavteluri (55/55), Besikuri (5/4/5), etc. The first Georgian treatise on versification written by Mamuka Baratashvili Chashniki anu leksis stsavlis tsigni (1731) preserves even now not only historical but theoretical value during determination of the nature of Georgian verse. The first half of the 20th century marks the beginning of a new stage in Georgian versification with Sergi Gorgadze’s “Georgian Verse” (1930), the second half of the 20th century – Akaki Gatserelia’s “Georgian Classical Verse” (1953) and the beginning of the 21st century - Akaki Khintibidze’s monograph “The History and Theory of Georgian Verse” (2009). On the path to scholarly research into Georgian verse the most important question still remains the establishment of the nature of national versification: due to the peculiarity of phonological system of Georgian language, it is neither syllabic nor syllabo-tonic, and that is why it is hard to place it in some known systems of versification.